2022
DOI: 10.3390/rs14215436
|View full text |Cite
|
Sign up to set email alerts
|

A New Algorithm of Atmospheric Boundary Layer Height Determined from Polarization Lidar

Abstract: Accurately determining the atmospheric boundary layer height (ABLH) is needed when one is addressing the air quality-related issues in highly urbanized areas, as well as when one is investigating issues that are related to the emission and transport of dust aerosols over the source region. In this study, we propose a new ABLH retrieval method, which is named ADEILP (ABLH that is determined by polarization lidar); it is based on the short-term polarized lidar observation that took place during the intensive fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…A possible reason is associated with the particle emission mechanism being closely related to WS over dust source areas, unlike the emissions in urban areas. The maximum atmosphere boundary layer height (ABLH) in TZ occurred at approximately 16:00 h in the day [51,52]. This strong thermal mixing within the atmosphere boundary layer (ABL) uplifted the near-surface particles to higher altitudes, resulting in a decrease in the mass concentration and PNC near the surface.…”
Section: Diurnal Evolutionmentioning
confidence: 99%
“…A possible reason is associated with the particle emission mechanism being closely related to WS over dust source areas, unlike the emissions in urban areas. The maximum atmosphere boundary layer height (ABLH) in TZ occurred at approximately 16:00 h in the day [51,52]. This strong thermal mixing within the atmosphere boundary layer (ABL) uplifted the near-surface particles to higher altitudes, resulting in a decrease in the mass concentration and PNC near the surface.…”
Section: Diurnal Evolutionmentioning
confidence: 99%
“…Zhang et al [38] used the meteorological data of five stations around the TD to find that sand and dust aerosols promote the development of the SBLH by adjusting the surface and atmospheric radiation budget. Han et al [39] proposed a new boundary layer height calculation method using polarized lidar to estimate the SBLH of the TD, and they found that the SBLH was overestimated and the height of the hybrid layer was underestimated. Studies have deepened our understanding of the structure and characteristics of the SBL in the desert hinterland, but the mechanism through which the SBLH forms in the TD hinterland is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%